2023
DOI: 10.21608/ejnf.2023.298115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirulina Platensis Algae Supplementation on Growth Performance, Physiological Status of Broilers During Summer Season

Abstract: he current study was designed to investigate the effects of dietary Spirulina inclusion at different levels on growth performance, antioxidant status, carcass traits and blood hematology of broilers subjected to cyclic heat stress. A total of 150 one-day-old Ross broiler chicks were randomly divided into three experimental groups with 5 replicates with 10 birds for each. The first group was provided with a basal diet and served as a control. Meanwhile, others were fed a basal diet supplemented with Spirulina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In broiler chickens, previous studies found that low inclusion levels (0.015–1.0%) of C. vulgaris improved performance ( An et al, 2016 ; Abdelnour et al, 2019 ; El-Bahr et al, 2020 ), whereas higher levels (10%) had positive effects on hepatic antioxidant capacity and meat quality ( Alfaia et al, 2021 ; Coelho et al, 2021 ; Boskovic Cabrol et al, 2022a ; Boskovic Cabrol et al, 2022b ). Spirulina microalgae supplementation in water (5–20 g/L) ( Kolluri et al, 2022 ) or feed (1–2 g/kg) ( Elbaz et al, 2022 ; Abed et al, 2023 ) also improved performance, immunity, and antioxidant status in chickens under heat stress. Then, available studies about the impact of C. vulgaris on meat quality traits ( El-Bahr et al, 2020 ; Alfaia et al, 2021 ; Boskovic Cabrol et al, 2022b ) emphasized the positive effects on meat fortification with pigments and n3 polyunsaturated fatty acids ( PUFA ).…”
Section: Introductionmentioning
confidence: 99%
“…In broiler chickens, previous studies found that low inclusion levels (0.015–1.0%) of C. vulgaris improved performance ( An et al, 2016 ; Abdelnour et al, 2019 ; El-Bahr et al, 2020 ), whereas higher levels (10%) had positive effects on hepatic antioxidant capacity and meat quality ( Alfaia et al, 2021 ; Coelho et al, 2021 ; Boskovic Cabrol et al, 2022a ; Boskovic Cabrol et al, 2022b ). Spirulina microalgae supplementation in water (5–20 g/L) ( Kolluri et al, 2022 ) or feed (1–2 g/kg) ( Elbaz et al, 2022 ; Abed et al, 2023 ) also improved performance, immunity, and antioxidant status in chickens under heat stress. Then, available studies about the impact of C. vulgaris on meat quality traits ( El-Bahr et al, 2020 ; Alfaia et al, 2021 ; Boskovic Cabrol et al, 2022b ) emphasized the positive effects on meat fortification with pigments and n3 polyunsaturated fatty acids ( PUFA ).…”
Section: Introductionmentioning
confidence: 99%